Concept of Family Education in Islamic Perspective - Kusrini, Eni (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
According to the Islamic view, children's first and foremost education is education in the family. Following the Islamic view, education in the family is based on Islamic religious guidance applied in the family and intended to shape children into human beings who believe and are devoted to God Almighty and have a noble character in everyday life. The research method used is literature study, namely the study of books, articles, and other literature related to the researched theme i. Family education aims to create an educational environment for children as students in the family, where parents act as educators and have a crucial role in determining the future children's lives. So that the very essence of family education is to carry out the process of installing Islamic values in the form of faith, worship, and moral education carried out by parents to their children as a process of regeneration in the family.